POLYURETHANE COMPOSITES AS DRUG CARRIERS:: RELEASE PATTERNS - M. V. Grigoreva (Biotechnologia Acta, 2013)
Biodegradable polyurethanes attract interest of those developing composite materials for biomedical applications. One of their features is their ability to serve as carriers, or matrixes, for medicines and other bioactive compounds to produce a therapeutic effect in body through targeted and/or prolonged delivery of these compounds in the process of their controlled release from matrix. The review presents polyurethane composites as matrices for a number of drugs. The relation between structure of the composites and their degradability both in vitro and in vivo and the dependence of drug release kinetics on physicochemical properties of polyurethane matrix are highlighted. The release of drugs (cefazolin, naltrexone and piroxicam) from the composites based on cross-linked polyurethanes (synthesized from laprols, Mw between 1,500 and 2,000 Da and toluylene diisocyanate) demonstrated more or less the same pattern (about 10 days in vitro and three to five days in vivo). In contrast, the composites with dioxydine based on a linear polyurethanes (synthesized from oligotetramethilene glycol, Mw 1,000 Da, diphenylmethane-4,4’-diisocyanate and 1,4-butanediol) retained their antimicrobial activity at least 30 days. They also showed a significantly higher breaking strength as compared to that of the composites based on cross-linked polyurethanes.